Cylindrical lithium ion battery and power-using device

By optimizing the structure and materials of lithium-ion batteries and adjusting internal resistance and heat dissipation performance, the problem of temperature increase of batteries under high power conditions is solved, achieving more efficient energy emission and longer service life.

CN119742418APending Publication Date: 2025-04-01JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411935154.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Under high power conditions, the internal resistance of the lithium-ion battery causes the conversion of electrical energy into thermal energy, causing temperature increases and energy loss, which in turn affects the safety and service life of the battery.

Method used

By optimizing the structure and materials of the battery, specific measures include adjusting the relationship between AC internal resistance, DC internal resistance and temperature rise coefficient, enhancing the heat dissipation performance of the battery, reducing the internal resistance of the battery, and improving the high-rate charging and discharge performance of the battery through the all-pole ear design and a reasonable combination of materials.

Benefits of technology

It effectively reduces the temperature rise rate of the battery during large-scale discharge, improves the discharge rate of the battery's internal energy, extends the service life of the battery, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742418A_ABST
    Figure CN119742418A_ABST
Patent Text Reader

Abstract

The present application proposes a cylindrical lithium-ion battery and an electrical device, wherein the cylindrical lithium-ion battery includes a shell, a winding core assembled in the shell, and an electrolyte filled in the shell, the AC internal resistance of the cylindrical lithium-ion battery is a milliohm, the DC internal resistance is b milliohm, the temperature rise coefficient of the cylindrical lithium-ion battery at a discharge rate of 10C is c K / (min*Ah), and the temperature rise coefficient and the AC internal resistance and the DC internal resistance satisfy the following relationship: 0.1≤[2a / (a+b)]*c≤4. By making the AC internal resistance, DC internal resistance and temperature rise coefficient of the cylindrical lithium-ion battery at a discharge rate of 10C satisfy a specific relationship, the operating temperature rise of the battery can be reduced under the condition of high-rate discharge of the battery, the cycle performance of the battery can be improved, and the total energy throughput of the battery can be increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrical devices, and in particular to a cylindrical lithium-ion battery and an electrical device. Background Art

[0002] With the improvement of science and technology, the popularity of high-power electrical appliances driven by secondary batteries in people's work and life has gradually increased, and the safety of secondary batteries used in electrical appliances has attracted more and more attention. Under high-power conditions, secondary batteries need to be discharged at a high rate. At this time, the internal resistance of the battery will cause part of the battery's electrical energy to be converted into heat energy, causing the battery temperature to rise and energy loss. In order to prevent the safety hazards caused by excessive battery temperature, electrical appliances usually set a temperature protection mechanism. Once the battery temperature reaches the set value, the appliance will automatically stop working. If the battery triggers the temperature protection due to excessive temperature rise under high-rate discharge conditions, and the appliance stops working prematurely, it will shorten the working time of a single use, affecting the user's actual work and usage experience.

[0003] The internal resistance of the battery follows Joule's law Q = I 2 Rt generates heat, where I is current, R is resistance, t is time, and Q is heat generation. Therefore, under high-rate discharge, reducing the internal resistance R of the battery is an effective way to reduce heat generation.

[0004] On the other hand, the continuous heat generation of the battery's internal resistance will cause the battery temperature to rise. The actual temperature rise of the battery is △T = △Q / C, where C is the heat capacity of the battery material and △Q is the difference between heat generation and heat dissipation. Therefore, by increasing the heat capacity of the battery material or enhancing the heat dissipation of the battery, the final temperature rise of the battery can also be improved.

[0005] Therefore, for cylindrical lithium-ion batteries with high-rate charge and discharge, it is necessary to reduce the internal resistance of the battery and reduce the heat generation, and to enhance the thermal capacity and / or heat dissipation of the battery material to control the temperature rise of the battery, so as to avoid overheating of the battery and trigger the temperature protection of the electrical device, and increase the actual discharge rate of the battery power; it can also prevent the battery from overheating and causing accelerated battery attenuation or even battery failure, thereby improving the battery life and safety performance. Summary of the invention

[0006] In order to solve the above problems, reduce the temperature rise rate of the battery during high-rate discharge, and increase the release rate of the battery's internal energy, the first aspect of the present application provides a cylindrical lithium-ion battery, including a shell, a winding core assembled in the shell, and an electrolyte filled in the shell, the AC internal resistance of the cylindrical lithium-ion battery is a milliohm, the DC internal resistance is b milliohm, and the temperature rise coefficient of the cylindrical lithium-ion battery at a discharge rate of 10C is c K / (min*Ah), and the temperature rise coefficient and the AC internal resistance and the DC internal resistance satisfy the following relationship: 0.1≤[2a / (a+b)]*c≤4. By making the AC internal resistance, DC internal resistance and temperature rise coefficient of the cylindrical lithium-ion battery at a discharge rate of 10C satisfy a specific relationship, it is possible to reduce the operating temperature rise of the battery without triggering the temperature protection condition when the battery is discharged at a high rate, thereby improving the release efficiency of the battery capacity.

[0007] In some optional embodiments, the temperature rise coefficient and the AC internal resistance and the DC internal resistance satisfy the following relationship: 0.2≤[2a / (a+b)]*c≤2. By further defining the relationship between the AC internal resistance, the DC internal resistance and the temperature rise coefficient at a discharge rate of 10C, the high-rate charge and discharge performance of the battery is further optimized, the temperature rise in the working state is reduced, and the cycle performance is improved, thereby increasing the total energy throughput of the battery during its life cycle.

[0008] In some optional embodiments, the cylindrical lithium-ion battery is placed in an AC impedance meter, and the AC internal resistance a of the cylindrical lithium-ion battery is measured at a frequency of 1000 Hz, in milliohms;

[0009] The acquisition of the DC internal resistance includes: at an experimental temperature of 25° C., charging the cylindrical lithium ion battery to a rated charging cut-off voltage of 4.2V at a charging rate of 2C, then charging at a constant voltage until the current drops to 0.025C, standing for 4 hours, discharging the cylindrical lithium ion battery at a discharge rate of 2.5C, continuously discharging for 10 seconds, then reducing the discharge rate to 0.25C, continuing to discharge for 10 seconds, and finally increasing the discharge rate again to 2.5C, continuously discharging for 4 seconds, and during the discharge process, recording the voltage (V1) at the 18th second and the voltage (V2) at the 23rd second. The DC internal resistance b is: b=(V1-V2) / 2.25C, in milliohms;

[0010] The acquisition of the temperature rise coefficient c includes: charging the cylindrical lithium ion battery to a rated charging cut-off voltage of 4.2V at a rate of 1C at a room temperature of 25°C, then charging at a constant voltage until the current is less than or equal to 0.05C, standing for 30 minutes, and then discharging at a rate of 0.2C to a discharge cut-off voltage of 2.5V, and recording the discharge capacity of the battery at this time as C0; standing the cylindrical lithium ion battery for 30 minutes, charging the cylindrical lithium ion battery again at a rate of 1C to a charging cut-off voltage of 4.2V, and charging at a constant voltage until the current is less than or equal to 0.05C; standing the cylindrical lithium ion battery for 30 minutes again, discharging at a rate of 10C to a discharge cut-off voltage of 2.5V and testing the battery temperature, if the battery surface temperature reaches 80°C, stop discharging, record the discharge time as t minutes, and the battery temperature rise value △T, the temperature rise coefficient c is: c=△T / (t*C0), in units of K / (min*Ah). The above method can be used to measure the battery's AC internal resistance a, DC internal resistance b and temperature rise coefficient c at a 10C discharge rate.

[0011] In some optional embodiments, after the cylindrical lithium-ion battery is charged and discharged 1000 times at a 1C charge rate and a 1C discharge rate, the longest diameter X1 and the shortest diameter Y1 of the orthographic projection of the shell in its axial direction satisfy: (X1-Y1) / (X1+Y1)≤5.5%. By restricting the deformation of the battery shell, the heat dissipation efficiency of the shell is enhanced.

[0012] In some optional embodiments, after the cylindrical lithium-ion battery is charged and discharged 1000 times at a 1C charge rate and a 1C discharge rate, the longest diameter X2 and the shortest diameter Y2 of the orthographic projection of the core in its axial direction satisfy: (X2-Y2) / (X2+Y2)≤9%. By restricting the deformation of the core of the battery, the heat dissipation efficiency of the core is enhanced.

[0013] In some optional embodiments, the weight of the copper foil in the core accounts for 8.5%-15% of the total weight of the cylindrical lithium-ion battery. By adding metallic copper to the core, the heat dissipation performance of the core is greatly improved by utilizing the good thermal conductivity of copper, and the copper content in the core is controlled to avoid excessive or heavy copper foil that affects the volume energy density and weight energy density of the battery.

[0014] In some optional embodiments, the winding core includes a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material coating coated on at least one surface of the positive electrode current collector, and a positive electrode empty foil area not coated with the positive electrode active material is reserved on the positive electrode current collector, and the positive electrode empty foil area is used as a positive electrode tab after winding, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active material coating located on at least one surface of the negative electrode current collector, and a negative electrode empty foil area not coated with the negative electrode active material is reserved on the negative electrode current collector, and the negative electrode empty foil area is used as a negative electrode tab after winding. By designing the full tabs of the positive and negative electrodes of the winding core, the internal resistance of the battery is greatly reduced, and the heat generation of the battery during high-rate charge and discharge is reduced.

[0015] In some optional embodiments, the positive electrode empty foil area accounts for 1%-10% of the positive electrode current collector area, and the negative electrode empty foil area accounts for 1%-10% of the negative electrode current collector area. By limiting the area of ​​the empty foil area on the positive and negative electrode sheets, it is possible to ensure that the positive and negative electrodes of the winding core are smoothly electrically connected to the external electrodes of the battery, minimize the internal resistance of the positive and negative electrode sheets, and avoid excessive temperature rise during high-rate charging and discharging; it is also possible to avoid an excessively high proportion of empty foil area, which will increase the weight and volume of inactive substances and affect the weight energy density and volume energy density of the battery.

[0016] In some optional embodiments, at least one side of the positive electrode active material coating is coated with an inorganic ceramic coating area. By coating at least one side of the positive electrode active material coating with an inorganic ceramic coating area, it is used as a barrier to prevent uncontrolled propagation of heat and current when abnormal conditions occur in the battery, such as overcharge, over discharge, short circuit, etc., and reduce the risk of thermal runaway.

[0017] In some optional embodiments, the width of the inorganic ceramic coating is 1%-5% of the width of the positive electrode sheet. If the width of the inorganic ceramic coating is too wide, the width of the active material coating of the positive electrode sheet will be reduced, thereby reducing the capacity of the winding core. Limiting the width of the inorganic ceramic coating to 1%-5% of the width of the positive electrode sheet can not only improve the safety of the battery, but also minimize the impact on the battery capacity.

[0018] In some optional embodiments, the inorganic ceramic coating is composed of one or more inorganic material particles selected from silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, iron trioxide, aluminum trioxide, manganese dioxide, magnesium oxide, boehmite, gypsum, talc, and calcite. The inorganic ceramic coating made of the above inorganic material particles has good thermal stability and can still play the role of electrical insulation in a high temperature environment; at the same time, it can provide mechanical support for the positive electrode active material coating and enhance the structural stability.

[0019] In some optional embodiments, the average particle size Dv50 of the inorganic material particles is 0.1-5 microns. Selecting inorganic material particles with an average particle size Dv50 of 0.1-5 microns to make an inorganic ceramic coating can form a more uniform coating, reduce coating pore defects, and have good coating quality and electrical insulation performance, which helps to improve the safety of the battery.

[0020] In some optional embodiments, the positive electrode active material is a nickel-based lithium-intercalated transition metal oxide material or a combination of a nickel-based lithium-intercalated transition metal oxide material and a lithium iron phosphate material, the metal elements in the nickel-based lithium-intercalated transition metal oxide material further include one or more of cobalt, manganese, and aluminum, and the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms is greater than or equal to 80%. By controlling the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms, the electron conductivity and ion diffusion in the coil core are enhanced, the impedance of the positive electrode sheet is reduced, the energy density of the battery charge and discharge process is increased, and high-rate charge and discharge are achieved.

[0021] In some optional embodiments, the negative electrode active material includes at least one of a silicon-based material and a carbon-based material, the silicon-based material includes one or more of a silicon-carbon material, a silicon-oxygen material or a single silicon material, the carbon-based material includes one or more of artificial graphite, natural graphite, hard carbon or soft carbon, and the mass of the silicon-based material accounts for 0%-30% of the mass of the negative electrode active material. By controlling the mass proportion of the silicon-based material in the negative electrode active material, on the one hand, the silicon-based material has a higher gram capacity than the carbon-based material, which can reduce the coating surface density and thickness of the negative electrode sheet, reduce the impedance of the negative electrode sheet, and improve the kinetic performance of the battery charge and discharge process. The specific energy of the cylindrical lithium-ion battery is increased to greater than or equal to 280Wh / kg, and high-rate charge and discharge are achieved; on the other hand, controlling the silicon content can inhibit the volume expansion due to the alloying of silicon and lithium, maintain the structural stability of the negative electrode active material, and thus ensure the cycle performance and safety of the battery.

[0022] The second aspect of the present application provides an electrical device, comprising any of the cylindrical lithium-ion batteries described above. Since the cylindrical lithium-ion battery has the above-mentioned beneficial effects, the electrical device provided by the present application has a lower temperature rise during high-rate discharge without triggering the temperature protection condition, or the battery capacity release efficiency is higher when the temperature protection condition is reached. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 It is a schematic structural diagram of a cylindrical lithium-ion battery according to an embodiment of the present application;

[0025] Figure 2 It is a structural schematic diagram of a cylindrical lithium-ion battery roll core according to an embodiment of the present application;

[0026] Figure 3 is an orthographic projection view of a cylindrical lithium-ion battery in an embodiment of the present application in the axial direction;

[0027] Figure 4 This is a front view of a positive electrode sheet of a cylindrical lithium-ion battery in one embodiment of the present application;

[0028] Figure 5 It is a front view of a negative electrode sheet of a cylindrical lithium-ion battery according to an embodiment of the present application;

[0029] Figure 6-Figure 7 It is a statistical chart of the test results of the discharge test performed on Example 1 of the present application and Comparative Example 1 according to the experimental conditions of Table 8.

[0030] Figure numerals: 1-shell, 2-winding core, 21-positive electrode sheet, 23-diaphragm, 25-negative electrode sheet, 210-positive electrode active material coating, 212-positive electrode empty foil area, 214-inorganic ceramic coating, 250-negative electrode active material coating, 252-negative electrode empty foil area. DETAILED DESCRIPTION

[0031] Embodiments of the present embodiment are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present embodiment, and should not be construed as limiting the present embodiment.

[0032] In the description of this embodiment, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this embodiment and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this embodiment.

[0033] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0034] In the description of this embodiment, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in this embodiment based on the specific content of the technical solution.

[0035] Please refer to Figure 1-Figure 2 , Figure 1 The figure shows a schematic diagram of the assembled structure of a cylindrical lithium-ion battery according to an embodiment of the present application. Figure 2 A schematic structural diagram of a winding core is shown.

[0036] Take the assembled cylindrical lithium-ion battery, place the cylindrical lithium-ion battery in an AC impedance meter, and measure the AC internal resistance a of the cylindrical lithium-ion battery at a frequency of 1000 Hz, in milliohms;

[0037] Take the assembled cylindrical lithium ion battery, charge the cylindrical lithium ion battery to a charging cut-off voltage of 4.2V at a charging rate of 2C at an experimental temperature of 25°C, then charge at a constant voltage until the current drops to 0.025C, let it stand for 4 hours, discharge the cylindrical lithium ion battery at a discharge rate of 2.5C, continue to discharge for 10 seconds, then reduce the discharge rate to 0.25C, continue to discharge for 10 seconds, and finally increase the discharge rate to 2.5C again, and continue to discharge for 4 seconds. During the discharge process, record the voltage V1 at the 18th second and the voltage V2 at the 23rd second. The DC internal resistance b can be calculated by b=(V1-V2) / 2.25C, in milliohms;

[0038] Take the assembled cylindrical lithium ion battery, charge the cylindrical lithium ion battery to a charging cut-off voltage of 4.2V at a rate of 1C at a room temperature of 25°C, then charge at a constant voltage until the current is less than or equal to 0.05C, stand for 30 minutes, and then discharge at a rate of 0.2C to a discharge cut-off voltage of 2.5V, and record the discharge capacity of the battery at this time as C0; stand the cylindrical lithium ion battery for 30 minutes, charge the cylindrical lithium ion battery again at a rate of 1C to a charging cut-off voltage of 4.2V, and charge at a constant voltage until the current is less than or equal to 0.05C; stand the cylindrical lithium ion battery for 30 minutes again, discharge at a rate of 10C to a discharge cut-off voltage of 2.5V and test the battery temperature. If the battery surface temperature reaches 80°C, stop discharging, record the discharge time as t minutes, and the battery temperature rise value △T, the temperature rise coefficient c is: c=△T / (t*C0), in units of K / (min*Ah).

[0039] Among them, the battery temperature is obtained by setting a temperature sensing line test on the battery surface, and the relationship between the charge rate and discharge rate and the charge / discharge current is: charge / discharge current = battery rated capacity × charge / discharge rate. For example, if the battery rated capacity is 4Ah and the discharge rate is 1C, the battery discharge current is 4A, the discharge rate is 2.5C, the battery discharge current is 10A, and the discharge rate is 10C, the battery discharge current is 40A.

[0040] It should be noted that the AC internal resistance and DC internal resistance of cylindrical lithium-ion batteries are both resistance parameters, but the test methods of the two are different, so there are slight differences in the physical meanings that can be expressed. The AC internal resistance a mainly includes the impedance with a faster response, which mainly affects the temperature rise in the early stage of high-rate charging; while the DC internal resistance b includes both the impedance with a faster response and the impedance with a slower response, which mainly affects the temperature rise in the middle stage. The temperature rise coefficient c directly reflects the battery's charge and discharge rate capabilities. When the value of the temperature rise coefficient c is too large, the battery is very likely to trigger the temperature protection condition during high-rate discharge, affecting the single working time of the appliance; when the value of the temperature rise coefficient c is too small, it may cause the battery to heat up too slowly and fail to obtain an appropriate operating temperature range, affecting the battery's efficiency.

[0041] Through the above tests, the AC internal resistance of the cylindrical lithium-ion battery is obtained to be a milliohms, the DC internal resistance is b milliohms, and the temperature rise coefficient at a discharge rate of 10C is c K / (min*Ah). The value of any one of a, b, and c or any two or more values ​​are further adjusted so that the temperature rise coefficient and the AC internal resistance and the DC internal resistance satisfy the following relationship: 0.1≤[2a / (a+b)]*c≤4.

[0042] Experiments have shown that by improving the battery structure and material system, the AC internal resistance, DC internal resistance and temperature rise coefficient of the cylindrical lithium-ion battery at a discharge rate of 10C meet the above specific relationship, reducing the temperature rise per unit time in the working state, reducing the frequency of triggering temperature protection, and improving the efficiency of battery discharge and charging before reaching the temperature protection value.

[0043] Furthermore, when the temperature rise coefficient c of the battery satisfies the following relationship with its AC internal resistance a and DC internal resistance b: 0.2≤[2a / (a+b)]*c≤2, the high-rate charge and discharge performance of the battery can be further optimized. When the battery is discharged at a rate of 10C, the operating temperature rise of the battery can be reduced by at least 30%, the total energy throughput of the battery can be increased by 80%, and the high cycle retention rate of the battery can be maintained at a charging rate of 3C or above. At a fast charging rate of 3C or above, the time required for the battery capacity to be charged from 0 to 80% of the maximum capacity is no more than 10 minutes.

[0044] It can be understood that the definition of the mathematical relationship between the temperature rise coefficient c of the battery and its AC internal resistance a and DC internal resistance b can be achieved through thermal management of the battery. The specific means correspond to enhancing the heat dissipation of the battery and reducing the internal resistance of the battery to reduce the heat generated by the battery during operation.

[0045] Specifically, in some optional embodiments, see Figure 3 , by constraining the deformation of the shell 1 and the core 2 compared to the perfect circular contour of the orthographic projection on the axial direction after manufacturing, the heat dissipation efficiency of the shell 1 and the core 2 is guaranteed. It can be understood that the shell 1 and the core 2 of the battery are cylindrical when they are manufactured, but with the charging and discharging operation of the battery, the positive / negative active materials on the core 2 will expand in volume, and stress will be generated between the core 2 and the shell 1, so some deformation will occur in the radial direction, and then the orthographic projection of the shell 1 and the core 2 on its axial direction will become a non-perfect circle approximate circle. For example, it is limited that the shell of a cylindrical lithium-ion battery is charged and discharged 1000 times at a 1C charging and 1C discharging rate. 1 and the deformation degree of the winding core 2, the longest diameter X1 and the shortest diameter Y1 of the orthographic projection of the constraint shell 1 meet: (X1-Y1) / (X1+Y1)≤5.5%, the longest diameter X2 and the shortest diameter Y2 of the orthographic projection of the winding core 2 meet: (X2-Y2) / (X2+Y2)≤9%, the circularity of the shell 1 and the winding core 2 is good, and the contact area between the two or between the two and other heat conduction parts is also larger, which is conducive to the rapid transfer of heat. At the same time, the regular shape of the winding core 2 and the shell 1 is conducive to the uniform distribution of heat inside the battery and the uniformity of thermal expansion, reducing the generation of local hot spots and the mechanical stress and potential damage caused by thermal expansion.

[0046] In other optional embodiments, the heat dissipation of the battery can be enhanced by adjusting the material system. The core 2 is made of copper foil. The good thermal conductivity of copper is utilized to greatly improve the heat dissipation performance of the core 2. At the same time, the weight of the copper foil is limited to 8.5%-15% of the total weight of the battery. The copper foil content in the battery is controlled to avoid excessive or heavy copper foil affecting the volume energy density and weight energy density of the battery.

[0047] In the specific implementation process, the copper foil content in the battery is mainly achieved by using copper foil to make the negative electrode current collector. Correspondingly, the method for determining the copper foil content of the battery is:

[0048] Step 1: Determine the battery mass M1;

[0049] Step 2: Disassemble the battery and obtain the negative electrode sheet 25;

[0050] Step 3: Place the negative electrode sheet 25 into a muffle furnace protected by nitrogen, set the furnace temperature to 300° C., and calcine the negative electrode sheet 25 for six hours;

[0051] Step 4: Cool the calcined negative electrode sheet 25 to room temperature, and remove the negative electrode active material coating 250 on the surface of the negative electrode sheet 25 with a brush;

[0052] Step 5: washing the treated negative electrode sheet 25 three times with deionized water to obtain a negative electrode current collector;

[0053] Step 6: Place the washed negative electrode current collector in a vacuum oven and bake at 60°C for 6 hours;

[0054] Step 7: Weigh the mass of the negative electrode current collector after drying as M2, and obtain the percentage of copper foil content: M2 / M1×100%.

[0055] In some alternative embodiments, see Figure 4 and Figure 5 By reserving a positive electrode empty foil area 212 and a negative electrode empty foil area 252 on the positive electrode sheet 21 and the negative electrode sheet 25 respectively, a positive electrode tab or a negative electrode tab is formed after the winding core 2 is wound. This full-tab design for the electrode of the winding core 2 optimizes the electron channel path, greatly reduces the internal resistance of the battery, and reduces the heat generation of the battery during high-rate charging and discharging.

[0056] Furthermore, the positive electrode empty foil area 212 is limited to 1%-10% of the surface area of ​​the positive electrode collector, and the negative electrode empty foil area 252 is limited to 1%-10% of the surface area of ​​the negative electrode collector. The positive electrode empty foil area 212 and the negative electrode empty foil area 252 are usually made of conductive metal with good heat dissipation performance. Increasing the area of ​​the positive and negative electrode empty foil areas can enhance the heat dissipation performance of the core 2; at the same time, the positive and negative electrode empty foil areas will also be used to make positive electrode ears and negative electrode ears. Therefore, the larger the area of ​​the empty foil area, the smaller the resistance of the ears of the core 2, thereby reducing the heat generated when the core 2 is working; but if the area of ​​the empty foil area is too large, the mass of the inactive substance will increase, and it may also cause the coating area of ​​the positive and negative active substances to become smaller, thereby reducing the energy density of the core 2. The area of ​​the empty foil area is limited to 1%-10% of the surface area of ​​the collector, thereby enhancing the heat dissipation of the core 2, reducing the internal resistance of the ears, and ensuring the capacity of the battery.

[0057] Furthermore, at least one side of the positive electrode active material coating 210 is coated with an inorganic ceramic coating 214, which can serve as a barrier to prevent the uncontrollable propagation of heat and current when the battery is in abnormal condition, such as overcharge, over discharge, short circuit, etc., and reduce the risk of thermal runaway; preferably, the inorganic ceramic coating 214 is coated on one side of the positive electrode active material coating 210 close to the positive electrode empty foil area 212 and extends onto the positive electrode empty foil area 212. By coating the inorganic ceramic coating 214 on the edge of the positive electrode active material coating 210 to connect the positive electrode empty foil area 212, it is prevented that the burrs generated when cutting the positive electrode empty foil area 212 to form the positive electrode ear pierce the diaphragm, causing a short circuit inside the battery. In addition, if the width of the inorganic ceramic coating 214 is too wide, the width of the positive electrode active material coating 210 will be reduced, thereby reducing the capacity of the core 2. Limiting the width of the inorganic ceramic coating 214 to 1%-5% of the width of the positive electrode sheet 21 can not only improve the safety of the battery, but also minimize the impact on the battery capacity.

[0058] In the specific implementation process, the inorganic ceramic coating 214 can be composed of one or more inorganic material particles of silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, iron trioxide, aluminum trioxide, manganese dioxide, magnesium oxide, boehmite, gypsum, talc, and calcite, and the average particle size Dv50 of each inorganic material particle is 0.1-5μm. The above-mentioned inorganic material particles have good thermal stability, and the selection of a suitable particle size can form a more uniform coating, reduce coating pore defects, have better thermal stability, and help improve the safety and cycle stability of the battery. It is understandable that if the size of the inorganic material particles is too large, the uniformity is poor, and the overall flatness and good fitting surface of the pole piece cannot be guaranteed. The formed inorganic ceramic coating 214 has poor adhesion and is easy to fall off; if the size of the inorganic material particles is too small, the inorganic ceramic coating 214 is too dense, the pole piece is difficult to process, and it is easy to lose powder.

[0059] In some optional embodiments, the positive electrode active material coated on the positive electrode sheet 21 is a nickel-based lithium-intercalated transition metal oxide material or a combination of a nickel-based lithium-intercalated transition metal oxide material and a lithium iron phosphate material. The metal elements in the nickel-based transition metal oxide material also include one or more of cobalt, manganese, and aluminum, and the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms is greater than or equal to 80%. By controlling the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms, the electronic conductivity and ion diffusion of the winding core 2 are enhanced, the impedance of the positive electrode sheet 21 is reduced, the energy density of the battery charging and discharging process is increased, and high-rate charging and discharging is achieved. Among them, the nickel-based lithium-intercalated transition metal oxide material can be one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, lithium nickel cobalt aluminum oxide, and lithium nickel manganese oxide, and the lithium iron phosphate material can be lithium iron phosphate and / or lithium manganese iron phosphate.

[0060] In some optional embodiments, the negative electrode active material coated on the negative electrode sheet 25 includes at least one of a silicon-based material and a carbon-based material, the silicon-based material includes one or more of a silicon-carbon material, a silicon-oxygen material or a single silicon material, the above silicon-based materials are all purchased from outside, the carbon-based material includes one or more of artificial graphite, natural graphite, hard carbon or soft carbon, and the mass proportion of the silicon-based material in the negative electrode active material is 0%-30%. By controlling the mass proportion of the silicon-based material in the negative electrode active material, on the one hand, the silicon-based material has a higher gram capacity than the carbon-based material, which can reduce the coating surface density and thickness of the negative electrode sheet, reduce the impedance of the negative electrode sheet, improve the kinetic performance of the battery charge and discharge process, and achieve high-rate charge and discharge; on the other hand, controlling the silicon content can inhibit the volume expansion degree due to the alloying of silicon and lithium, maintain the structural stability of the negative electrode active material, thereby ensuring the cycle performance and safety of the battery.

[0061] Among them, the silicon-based material can be elemental silicon and / or silicon oxide. Usually, the elemental silicon will also be subjected to carbon coating treatment. By coating the surface of the elemental silicon with amorphous carbon and / or carbon nanotubes, the interface stability and conductivity of the elemental silicon are improved, thereby improving the film integrity of the SEI film (Solid Electrolyte Interface, which is a passivation layer covering the surface of the electrode material formed during the first charge and discharge process of a lithium-ion battery) and improving the battery's cycle and safety performance.

[0062] Carbon-based materials can be a mixture of one or more of artificial graphite, natural graphite, hard carbon, and soft carbon. Artificial graphite refers to graphite materials manufactured by artificial synthesis methods, such as obtained by high temperature and high pressure treatment of carbon materials (such as graphite ore, coke, etc.) or chemical synthesis methods. It has strong consistency in morphology and particle size distribution, and the structure can be in various forms, such as block, fiber or powder; natural graphite refers to graphite formed naturally in nature, mainly in the form of ores such as graphite schist, graphite gneiss, graphite-containing schist and metamorphic shale; hard carbon refers to carbon that is difficult to graphitize, which is usually obtained by thermal decomposition of polymers, such as resin carbon, organic polymer pyrolytic carbon and carbon black; soft carbon refers to easily graphitized carbon, that is, amorphous carbon that can be graphitized at high temperatures above 2500°C. Common soft carbons include petroleum coke, needle coke, carbon fiber, carbon microspheres, etc.

[0063] In the specific implementation process, see Figure 4 and Figure 5 The positive electrode sheet 21 includes a positive electrode collector and a positive electrode active material coating 210 coated on at least one surface of the positive electrode collector. The positive electrode active material coating 210 is formed by coating a slurry formed by mixing a positive electrode active material, a binder, a conductive agent and a solvent on the surface of the positive electrode collector and then drying. The negative electrode sheet 25 includes a negative electrode collector and a negative electrode active material coating 250 coated on at least one surface of the negative electrode collector. The negative electrode active material coating 250 is formed by coating a slurry formed by mixing a negative electrode active material, a binder, a conductive agent and a solvent on the surface of the negative electrode collector and then drying.

[0064] In a specific implementation process, a method for manufacturing the positive electrode sheet 21 is as follows:

[0065] Aluminum foil is used as the positive electrode current collector, and the positive electrode active material coating 210 is composed of 97% of lithium nickel cobalt manganese oxide, 0.4% of single-walled carbon nanotube conductive agent, 1.6% of Super-P (conductive carbon black) conductive agent and 1% of polyvinylidene fluoride PVDF binder. The above substances are added to NMP solvent and mixed evenly to obtain a positive electrode slurry with a solid content of 60%. The positive electrode slurry is coated on the surface of the positive electrode current collector and the solvent is dried to obtain the positive electrode active material coating 210.

[0066] A method for manufacturing a negative electrode sheet 25:

[0067] Copper foil is used as the negative electrode current collector, and the negative electrode active material is coated with 96% artificial graphite, 1.0% conductive agent acetylene black, 1% thickener CMC and 2% negative electrode binder polyacrylic acid. The above substances are added to deionized water and mixed evenly to obtain a negative electrode slurry with a solid content of 40%. The negative electrode slurry is coated on the surface of the negative electrode current collector and dried to obtain a negative electrode sheet 25.

[0068] The shell 1 should also be filled with electrolyte. A method for preparing the electrolyte is as follows:

[0069] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0070] There should also be a separator 23 between the positive electrode sheet 21 and the negative electrode sheet 25. A method for making the separator 23 is as follows:

[0071] A PE film with a thickness of 9 μm was used as a base film, and a ceramic coating and a polyvinylidene fluoride PVDF coating with a thickness of 1 μm were coated on both sides to form a diaphragm 23, and the air permeability of the diaphragm 23 was controlled to be ≤100 s / 100 mL.

[0072] The assembly process of a cylindrical lithium-ion battery is as follows:

[0073] The positive electrode sheet 21 and the negative electrode sheet 25 are rolled, slit and die-cut respectively, and then wound together with the separator 23 to obtain a cylindrical winding core 2. The pole ears at both ends of the winding core 2 are welded to the electrical connecting sheet and loaded into the battery housing 1. After completing the injection, sealing and formation processes, a cylindrical lithium-ion battery is obtained.

[0074] The second aspect of the present application provides an electrical device, comprising any of the cylindrical lithium-ion batteries described above. Since the cylindrical lithium-ion battery has the above-mentioned beneficial effects, the electrical device provided by the present application heats up more slowly during high-rate discharge, and the energy loss of the battery due to heat generation is lower.

[0075] The following experiment is conducted on 21700 and 4695 lithium-ion batteries, where the diameter of the 21700 lithium-ion battery is 21 mm and the length is 70 mm; the diameter of the 4695 lithium-ion battery is 46 mm and the length is 95 mm. Specific embodiment 1:

[0077] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material NCA88: Li[Ni 0.88 Co 0.10 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.2mm and the shortest diameter Y1 is 19.7mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.67%; the longest diameter X2 of the core appearance is 20.95mm and the shortest diameter Y2 is 18.69mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.70%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 3mΩ, the DC internal resistance b is 7mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 31.2K; the temperature rise coefficient c is 1.30K / (min*Ah); then 2a*c / (a+b)=0.78. Specific embodiment 2:

[0079] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.1mm and the shortest diameter Y1 is 19.5mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.94%; the longest diameter X2 of the core appearance is 20.88mm and the shortest diameter Y2 is 17.68mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 8.30%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 3.1mΩ, the DC internal resistance b is 7.1mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 40K; the temperature rise coefficient c is 2.50K / (min*Ah); then 2a*c / (a+b)=1.52. Specific embodiment 3:

[0081] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.3mm and the shortest diameter Y1 is 19.4mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 4.67%; the longest diameter X2 of the core appearance is 20.91mm and the shortest diameter Y2 is 18.28mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 6.71%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 3mΩ, the DC internal resistance b is 6.8mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 44K; the temperature rise coefficient c is 1.83K / (min*Ah); then 2a*c / (a+b)=1.12. Specific embodiment 4:

[0083] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.2mm and the shortest diameter Y1 is 19.7mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.67%; the longest diameter X2 of the core appearance is 20.93mm and the shortest diameter Y2 is 18.69mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.65%; the copper foil content is 8.5wt%; the AC internal resistance a of the battery is 3.2mΩ, the DC internal resistance b is 7.4mΩ, the battery capacity C0 is 4Ah, the discharge time t is 4.7min, and the temperature rise △T is 55K; the temperature rise coefficient c is 2.93K / (min*Ah); then 2a*c / (a+b)=1.77. Specific embodiment 5:

[0085] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.1mm and the shortest diameter Y1 is 19.8mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.18%; the longest diameter X2 of the core appearance is 20.96mm and the shortest diameter Y2 is 18.72mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.65%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 2.5mΩ, the DC internal resistance b is 6mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 37K; the temperature rise coefficient c is 1.54K / (min*Ah); then 2a*c / (a+b)=0.91. Specific embodiment 6:

[0087] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.3mm and the shortest diameter Y1 is 19.7mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.90%; the longest diameter X2 of the core appearance is 20.96mm and the shortest diameter Y2 is 18.69mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.73%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 4mΩ, the DC internal resistance b is 12mΩ, the battery capacity C0 is 4Ah, the discharge time t is 3.7min, and the temperature rise △T is 55K; the temperature rise coefficient c is 3.72K / (min*Ah); then 2a*c / (a+b)=1.86. Specific embodiment 7:

[0089] Battery model: 21700; Tab design: full tab; Standard capacity: 5Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.4mm and the shortest diameter Y1 is 19.3mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 5.16%; the longest diameter X2 of the core appearance is 20.93mm and the shortest diameter Y2 is 18.71mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.60%; the copper foil content is 9.3wt%; the AC internal resistance a of the battery is 3.5mΩ, the DC internal resistance b is 8.4mΩ, the battery capacity C0 is 5Ah, the discharge time t is 6min, and the temperature rise △T is 50K; the temperature rise coefficient c is 1.67K / (min*Ah); then 2a*c / (a+b)=0.98. Specific embodiment 8:

[0091] Battery model: 21700; Tab design: full tab; Standard capacity: 6Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.3mm and the shortest diameter Y1 is 19.4mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 4.67%; the longest diameter X2 of the core appearance is 20.95mm and the shortest diameter Y2 is 18.68mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.73%; the copper foil content is 8.9wt%; the AC internal resistance a of the battery is 4mΩ, the DC internal resistance b is 9.1mΩ, the battery capacity C0 is 6Ah, the discharge time t is 3.9min, and the temperature rise △T is 55K; the temperature rise coefficient c is 2.35K / (min*Ah); then 2a*c / (a+b)=1.44. Specific embodiment 9:

[0093] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCMA88: Li[Ni 0.88 Co 0.06 Mn 0.04 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.3mm and the shortest diameter Y1 is 19.5mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 4.41%; the longest diameter X2 of the core appearance is 20.91mm and the shortest diameter Y2 is 18.71mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.55%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 3mΩ, the DC internal resistance b is 7mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 41K; the temperature rise coefficient c is 1.71K / (min*Ah); then 2a*c / (a+b)=1.03. Specific embodiment 10:

[0095] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCMA90: Li[Ni 0.90 Co 0.04 Mn 0.04 Al 0.02 ]O2; negative electrode material: 80wt% artificial graphite + 20wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.1mm and the shortest diameter Y1 is 19.8mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.18%; the longest diameter X2 of the core appearance is 20.91mm and the shortest diameter Y2 is 18.64mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.74%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 3mΩ, the DC internal resistance b is 7.2mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 39K; the temperature rise coefficient c is 1.63K / (min*Ah); then 2a*c / (a+b)=0.96. Specific embodiment 11:

[0097] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02]O2; negative electrode material: 100% artificial graphite; the longest diameter X1 of the shell appearance is 21.2mm and the shortest diameter Y1 is 19.8mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.41%; the longest diameter X2 of the core appearance is 20.99mm and the shortest diameter Y2 is 18.66mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.88%; the copper foil content is 8.9wt%; the AC internal resistance a of the battery is 3.3mΩ, the DC internal resistance b is 7.5mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 44K; the temperature rise coefficient c is 1.83K / (min*Ah); then 2a*c / (a+b)=1.12. Specific embodiment 12:

[0099] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon oxide material; the longest diameter X1 of the shell appearance is 21.2mm and the shortest diameter Y1 is 19.7mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.67%; the longest diameter X2 of the core appearance is 20.92mm and the shortest diameter Y2 is 18.69mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.36%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 2.9mΩ, the DC internal resistance b is 7mΩ, the battery capacity C0 is 4Ah, the discharge time t is 6min, and the temperature rise △T is 39K; the temperature rise coefficient c is 1.63K / (min*Ah); then 2a*c / (a+b)=0.95. Specific embodiment 13:

[0101] Battery model: 4695; Tab design: full tab; Standard capacity: 26Ah; Positive electrode material: NCMA88: Li[Ni 0.88 Co 0.06 Mn 0.04 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 46.3mm and the shortest diameter Y1 is 45.5mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 0.87%; the longest diameter X2 of the core appearance is 44.81mm and the shortest diameter Y2 is 42.98mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 2.08%; the copper foil content is 8.8wt%; the AC internal resistance a of the battery is 0.98mΩ, the DC internal resistance b is 2.31mΩ, the battery capacity C0 is 26Ah, the discharge time t is 6min, and the temperature rise △T is 39K; the temperature rise coefficient c is 0.25K / (min*Ah); then 2a*c / (a+b)=0.15.

[0102] Comparative Example 1:

[0103] Battery model: 21700; Tab design: 1+2 tabs; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.4mm and the shortest diameter Y1 is 19.7mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 4.14%; the longest diameter X2 of the core appearance is 20.94mm and the shortest diameter Y2 is 18.66mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.76%; the copper foil content is 9.7wt%; the AC internal resistance a of the battery is 12mΩ, the DC internal resistance b is 21mΩ, the battery capacity C0 is 4Ah, the discharge time t is 2.7min, and the temperature rise △T is 55K; the temperature rise coefficient c is 5.09K / (min*Ah); then 2a*c / (a+b)=3.70.

[0104] Comparative Example 2:

[0105] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.7mm and the shortest diameter Y1 is 19.1mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 6.37%; the longest diameter X2 of the core appearance is 20.91mm and the shortest diameter Y2 is 18.71mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.55%; the copper foil content is 9.5wt%; the AC internal resistance a of the battery is 3.3mΩ, the DC internal resistance b is 7.1mΩ, the battery capacity C0 is 4Ah, the discharge time t is 4.3min, and the temperature rise △T is 55K; the temperature rise coefficient c is 3.20K / (min*Ah); then 2a*c / (a+b)=2.03.

[0106] Comparative Example 3:

[0107] Battery model: 21700; Tab design: full tab; Standard capacity: 4Ah; Positive electrode material: NCA88: Li[Ni 0.88 Co 0.10 Al 0.02 ]O2; negative electrode material: 90wt% artificial graphite + 10wt% silicon carbon material; the longest diameter X1 of the shell appearance is 21.2mm and the shortest diameter Y1 is 19.7mm, and the deformation degree [(X1-Y1) / (X1+Y1)] is 3.67%; the longest diameter X2 of the core appearance is 20.95mm and the shortest diameter Y2 is 18.69mm, and the deformation degree [(X2-Y2) / (X2+Y2)] is 5.70%; the copper foil content is 8.1wt%; the AC internal resistance a of the battery is 3.6mΩ, the DC internal resistance b is 7.9mΩ, the battery capacity C0 is 4Ah, the discharge time t is 3.9min, and the temperature rise △T is 55K; the temperature rise coefficient c is 3.53K / (min*Ah); then 2a*c / (a+b)=2.21.

[0108] The above specific examples 1-13 and comparative examples 1-3 were subjected to 1C / 1C room temperature cycle capacity retention rate test and 3C / 6C fast charge cycle capacity retention rate test respectively:

[0109] The test method for 1C / 1C room temperature cycle capacity retention rate is:

[0110] Take a cylindrical lithium-ion battery prepared according to any of the above specific embodiments, place the battery in an environment of 25°C, and test it according to the following steps:

[0111] S1: Charge the battery at a constant current of 1C to the charging cut-off voltage, such as 4.20V, and then charge at a constant voltage to a current of 0.025C.

[0112] S2: Let stand for 15 minutes;

[0113] S3: Discharge the battery at a constant current of 1C to a discharge cut-off voltage, such as 2.5V;

[0114] S4: Let stand for 15 minutes;

[0115] S5: Perform multiple cycle charge and discharge tests on the battery according to steps S1 to S4; record the first discharge capacity of the battery as D1; ​​record the discharge capacity of the 500th cycle as D500;

[0116] S6: The normal temperature cycle capacity retention rate of the battery is obtained as: D500 / D1*100%.

[0117] The test method for 3C / 6C room temperature fast charging cycle capacity retention rate is:

[0118] Take a cylindrical lithium-ion battery prepared according to any of the above specific embodiments, place the battery in an environment of 25°C, and test it according to the following steps:

[0119] S11: Charge the battery at a constant current of 3C to a charging cut-off voltage, such as 4.20V.

[0120] S12: Let stand for 15 minutes;

[0121] S13: Discharge the battery at a constant current of 6C to a discharge cut-off voltage, such as 2.5V;

[0122] S14: Let stand for 15 minutes;

[0123] S15: Perform multiple cycle charge and discharge tests on the battery according to steps S11 to S14; record the first discharge capacity of the battery as D1, and record the discharge capacity of the 200th cycle as D200;

[0124] S16: The 3C fast charge / 6C fast discharge cycle capacity retention rate of the battery is obtained as: D200 / D1*100%.

[0125] Specific examples 1-3 and comparative example 2 are control groups with the deformation of the battery shell 1 and the winding core 2 as variables, specific examples 1, 4 and comparative example 3 are control groups with the copper foil content of the winding core 2 as variables, specific example 1 and specific examples 5-6 are control groups with the internal resistance of the battery as variables; specific example 1 and specific examples 7-8 are control groups with the battery capacity as variables; specific example 1 and specific examples 9-12 are control groups with the electrochemical system of the battery as variables; specific example 1 and specific example 13 are control groups with the battery size as variables; specific example 1 and comparative example 1 are control groups with the tab design as variables. Specific comparison results are shown in Tables 1-8:

[0126] Table 1:

[0127]

[0128] It can be seen from Table 1 that the deformation of the shell 1 and the core 2 has a strong correlation with the temperature rise per unit time. The smaller the deformation value, the closer the orthographic projection of the core 2 or the shell 1 is to a perfect circle. At the same time, the smaller the temperature rise per unit time, the higher the capacity retention rate of the battery.

[0129] Table 2:

[0130]

[0131]

[0132] It can be seen from Table 2 that the higher the copper foil content, the faster the heat dissipation of the battery, the smaller the temperature rise per unit time, and the higher the capacity retention rate of the battery.

[0133] Table 3:

[0134]

[0135] It can be seen from Table 3 that, in general, the greater the internal resistance of the battery, the greater the temperature rise per unit time, and the worse the battery capacity retention rate.

[0136] Table 4:

[0137]

[0138] It can be seen from Table 4 that the larger the battery capacity, the greater the temperature rise per unit time, and the worse the battery capacity cycle retention rate.

[0139] Table 5:

[0140]

[0141]

[0142] It can be seen from Table 5 that the capacity retention rate of the positive electrode active material using NCA88 with a nickel molar content of 88% is better than that of NCMA88 with the same nickel content; the capacity retention rate of the negative electrode active material using a mixed system of artificial graphite plus silicon-carbon material is better than that of a single artificial graphite system or a mixed system of artificial graphite and silicon-oxygen material, especially at high rate charge and discharge.

[0143] Table 6:

[0144]

[0145] It can be seen from Table 6 that the present application achieves better cycle capacity retention rate when the battery capacity is smaller and the internal resistance is relatively larger through thermal management of the battery.

[0146] Table 7:

[0147]

[0148] Among them, the 1+2 tab design means that one tab is set on one electrode of the battery and two tabs are set on the other electrode.

[0149] It can be seen from Table 7 that the full-ear design reduces the battery internal resistance by more than 70% compared with the 1+2-ear design. The temperature rise coefficient of Example 1 is 1.30K / (min*Ah), and the temperature rise coefficient of Comparative Example 1 is 5.09K / (min*Ah), with a reduction of more than 74%.

[0150] In addition, the following data were obtained from the 10C discharge rate test of Example 1 and Comparative Example 1:

[0151] Table 8:

[0152]

[0153] The statistical graph was obtained with reference to Table 8. Figure 6 The relationship between the battery discharge capacity and the battery surface temperature in Example 1 and Comparative Example 1 is reflected. Figure 7 The relationship between the battery discharge capacity and the battery voltage in Example 1 and Comparative Example 1 is reflected:

[0154] from Figure 6 It can be seen from the battery temperature and discharge capacity curves of Example 1 and Comparative Example 1 before the battery temperature reaches 80°C at 10C discharge. The full-ear cylindrical battery of Example 1 is discharged at 10C without triggering the set temperature upper limit of 80°C, and can discharge 3.95Ah of electricity, close to 4Ah, and the battery surface temperature is only 56.2°C, while the traditional pole ear cylindrical battery of Comparative Example 1 is discharged at 10C, and can only discharge 2.81Ah of electricity when the battery surface temperature reaches 80°C, which seriously reduces the battery capacity utilization efficiency and limits the battery usage scenario. After calculation, the temperature rise coefficient of the full-ear cylindrical lithium-ion battery in Example 1 reaches 1.30K / (min*Ah) at a rate of 10C, while the temperature rise coefficient of the traditional pole ear cylindrical lithium-ion battery in Comparative Example 1 reaches 5.09K / (min*Ah), which is much larger than the value of Example 1. It can be seen that the temperature rise of the traditional pole ear cylindrical lithium-ion battery is too high, which reduces the battery capacity utilization efficiency.

[0155] from Figure 7It can be seen from the battery voltage and discharge capacity curves of Example 1 and Comparative Example 1 before the battery temperature reaches 80°C when discharged at 10C. The full-ear cylindrical lithium-ion battery of Example 1 is discharged at 10C without triggering the set temperature upper limit of 80°C, and can discharge 3.95Ah of electricity, and the voltage drops to 2.5V, reaching the termination voltage. However, the traditional ear cylindrical lithium-ion battery of Comparative Example 1 is discharged at 10C, and can only discharge 2.81Ah of electricity when the battery surface temperature reaches 80°C, and the voltage reaches 3.05V, which does not reach the termination voltage, resulting in incomplete release of the battery capacity.

[0156] In the description of this specification, reference to the terms "some embodiments", "an example", or similar descriptions means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment or example. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0157] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.

Claims

1. A cylindrical lithium-ion battery, comprising a shell, a winding core assembled in the shell, and an electrolyte filled in the shell, characterized in that: The AC internal resistance of the cylindrical lithium ion battery is a milliohms, the DC internal resistance is b milliohms, the temperature rise coefficient of the cylindrical lithium ion battery at a discharge rate of 10C is cK / (min*Ah), and the temperature rise coefficient and the AC internal resistance and the DC internal resistance satisfy the following relationship: 0.1≤[2a / (a+b)]*c≤4.

2. The cylindrical lithium-ion battery according to claim 1, characterized in that: The temperature rise coefficient and the AC internal resistance and the DC internal resistance satisfy the following relationship: 0.2≤[2a / (a+b)]*c≤2.

3. The cylindrical lithium-ion battery according to claim 1 or 2, characterized in that: The cylindrical lithium-ion battery is placed in an AC impedance meter, and the AC internal resistance a of the cylindrical lithium-ion battery is measured at a frequency of 1000 Hz, in milliohms; The acquisition of the DC internal resistance includes: at an experimental temperature of 25° C., charging the cylindrical lithium ion battery at a charging rate of 2C to a charging cut-off voltage of 4.2V, then charging at a constant voltage to a current less than or equal to 0.025C, standing for 4 hours, discharging the cylindrical lithium ion battery at a discharge rate of 2.5C, continuously discharging for 10 seconds, then reducing the discharge rate to 0.25C, continuing to discharge for 10 seconds, and finally increasing the discharge rate to 2.5C again, continuously discharging for 4 seconds, and during the discharge process, recording the voltage V1 at the 18th second and the voltage V2 at the 23rd second, the DC internal resistance b is: b=(V1-V2) / 2.25C, in milliohms; The acquisition of the temperature rise coefficient c includes: charging the cylindrical lithium ion battery at a rate of 1C to a charging cut-off voltage of 4.2V at a normal temperature of 25°C, and then charging at a constant voltage until the current is less than or equal to 0.05C; after standing for 30 minutes, discharging at a rate of 0.2C to a discharge cut-off voltage of 2.5V, and recording the discharge capacity of the battery at this time as C0; standing the battery for 30 minutes, charging the cylindrical lithium ion battery again at a rate of 1C to a charging cut-off voltage of 4.2V, and then charging at a constant voltage until the current is less than or equal to 0.05C; standing the cylindrical lithium ion battery for 30 minutes again, discharging at a rate of 10C to a discharge cut-off voltage of 2.5V and testing the battery surface temperature, if the battery surface temperature reaches 80°C, stop discharging, record the discharge time as t minutes, and the battery temperature rise value △T, the temperature rise coefficient c can be obtained by c=△T / (t*C0), the unit is K / (min*Ah).

4. The cylindrical lithium-ion battery according to claim 1, characterized in that: After the cylindrical lithium-ion battery is cycled and discharged 1000 times at a 1C charge and 1C discharge rate, the longest diameter X1 and the shortest diameter Y1 of the orthographic projection of the shell in its axial direction satisfy the following conditions: (X1-Y1) / (X1+Y1)≤5.5%.

5. The cylindrical lithium-ion battery according to claim 4, characterized in that: After the cylindrical lithium-ion battery is charged and discharged 1000 times at a 1C charge rate and a 1C discharge rate, the longest diameter X2 and the shortest diameter Y2 of the orthographic projection of the winding core in its axial direction satisfy the following conditions: (X2-Y2) / (X2+Y2)≤9%.

6. The cylindrical lithium-ion battery according to claim 1, characterized in that: The weight of the copper foil in the winding core accounts for 8.5%-15% of the total weight of the cylindrical lithium-ion battery.

7. The cylindrical lithium-ion battery according to claim 1, characterized in that: The winding core includes a positive electrode sheet, a separator and a negative electrode sheet which are stacked, the positive electrode sheet includes a positive electrode collector and a positive electrode active material coating coated on at least one surface of the positive electrode collector, and a positive electrode empty foil area which is not coated with the positive electrode active material is reserved on the positive electrode collector, and the positive electrode empty foil area is used as a positive electrode tab after winding, the negative electrode sheet includes a negative electrode collector and a negative electrode active material coating located on at least one surface of the negative electrode collector, and a negative electrode empty foil area which is not coated with the negative electrode active material is reserved on the negative electrode collector, and the negative electrode empty foil area is used as a negative electrode tab after winding.

8. The cylindrical lithium-ion battery according to claim 7, characterized in that: The positive electrode empty foil area accounts for 1%-10% of the surface area of ​​the positive electrode current collector, and the negative electrode empty foil area accounts for 1%-10% of the surface area of ​​the negative electrode current collector.

9. The cylindrical lithium-ion battery according to claim 7, characterized in that: At least one side of the positive electrode active material coating is coated with an inorganic ceramic coating.

10. The cylindrical lithium-ion battery according to claim 9, characterized in that: The width of the inorganic ceramic coating is 1%-5% of the width of the positive electrode sheet.

11. The cylindrical lithium-ion battery according to claim 9, characterized in that: The inorganic ceramic coating is composed of one or more inorganic material particles selected from the group consisting of silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, aluminum oxide, magnesium oxide, boehmite, gypsum, talc and calcite.

12. The cylindrical lithium-ion battery according to claim 11, characterized in that: The average particle size Dv50 of the inorganic material particles is 0.1-5 microns.

13. The cylindrical lithium-ion battery according to claim 7, characterized in that: The positive electrode active material is a nickel-based lithium-intercalated transition metal oxide material or a combination of a nickel-based lithium-intercalated transition metal oxide material and a lithium iron phosphate material. The metal elements in the nickel-based lithium-intercalated transition metal oxide material also include one or more of cobalt, manganese, and aluminum, and the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms is greater than or equal to 80%.

14. The cylindrical lithium-ion battery according to claim 7, characterized in that: The negative electrode active material includes at least one of a silicon-based material and a carbon-based material, the silicon-based material includes one or more of a silicon-carbon material, a silicon-oxygen material or a single silicon material, the carbon-based material includes one or more of artificial graphite, natural graphite, hard carbon or soft carbon, and the mass of the silicon-based material accounts for 0%-30% of the mass of the negative electrode active material.

15. An electrical device, characterized in that: A cylindrical lithium-ion battery comprising any one of claims 1 to 14.

Citation Information

Cited By

  • Lightweight high-energy-density cylindrical lithium ion battery and electric equipment

    CN122494844A